Agentes de software: tecnologías, herramientas y aplicaciones - Roa, Olga Lucía (Universidad de San Buenaventura - Cali, 2017)
During their route through different systems, software agents have the possibility of obtaining services supplied locally in the visited systems and engaging in a dialog with other agents. These and other characteristics of the Multi-Agent Systems (MAS) make their design, implementation, maintenance, etc. a non trivial task. For this reason, it is desirable to count on tools that support the stages involved in the construction of MAS. This article presents a study on the current tools for the development of MAS, starting from their definition and the services they offer until the analysis of the technologies and tools used nowadays. At the end of the article a hypothesis on the trends of software construction is made.